Effect of Aerobic Packaging and Addition of Pomegranate Peel Extract on Physicochemical Characteristics of Ground Broiler Meat - Devatkal, S.K.; Rai , D.R.; Jaiswal , P. (Journal of Meat Science, 2011)
In this study effect of aerobic packaging and pomegranate peel extract on ground chicken meat during refrigerated storage was evaluated. Addition of extract increased the drip loss but did not affect the pH. Use of heat sealing and extract significantly reduced the TBARS values indicating antioxidant effect of pomegranate peel extract. Accumulation of CO2 was higher in aerobic packaged meat without heat sealing. Aerobic packaging was having beneficial effects in preserving the red colour and colour intensity of refrigerated stored chicken meat. It was concluded that addition of pomegranate peel extract improved the oxidative stability of aerobically packaged poultry meat.
Keywords: Poultry meat; pomegranate peel extract; head space gas; TBARS